Hyperoctahedral Schur algebras - Green, R (Elsevier, 1997)
We study the centralising algebra of a natural action of the hyperoctahedral group (i.e., a finite Weyl group of type Br) on the r-th tensor power of a 2n-dimensional space. The centralising algebra of this is shown to have a product rule similar to Schur's product rule in type A. We deform this action to an action of the Hecke algebra of type B and study the associated centralising algebra of type B and its dual. We introduce and study q-permutation modules for the algebra.